Pengembangan Usaha Melalui Inovasi Produk dan Pemasaran Media Sosial pada Usaha Mikro Kue Tradisional “ Puji Lestari “ di Menur Pumpungan Surabaya - Mataji Mataji; Sigit Santoso (Sekolah Tinggi Ilmu Administrasi Yappi Makassar, 2024)
Since the implementation of the ASEAN Economic Community (AEC) at the end of 2015, it should encourage all economic actors, including SMEs and Micro Enterprises, to improve themselves in order to improve the quality of production of both goods and services. If this is not done, then Indonesia will be an